Kecerdasan Adversitas dan Kematangan Karir Terhadap Intensi Berwirausaha - Agustina, Titien; Nasution, Muhammad Darwis; ., Sampurnawati (Sekolah Tinggi Ilmu Manajemen Indonesia (STIMI) Banjarmasin, 2018)
This study aims to examine the effect of adversity intelligence and career maturity on the intentions of entrepreneurship in working students. From this research is expected to reinforce the opinion that the students work has a career maturity and also a deeper endurance to bear the business uncertainty with the adversity of intelligence owned so as to strengthen the intentions of student entrepreneurship. The population of the study were 472. Working students of the Slovin formula obtained 83 respondents spread by purposive sampling through certain conditions. The results of research indicate that adversitas intelligence and career maturity, both partially and simultaneously show a positive influence to the intention of entrepreneurship.